2022
DOI: 10.1111/jeb.14013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methodological approaches to the study of young sex chromosomes: A case study in Poecilia

Abstract: Studies of sex chromosome systems at early stages of divergence are key to understanding the initial process and underlying causes of recombination suppression.However, identifying signatures of divergence in homomorphic sex chromosomes can be challenging due to high levels of sequence similarity between the X and the Y.Variations in methodological precision and underlying data can make all the difference between detecting subtle divergence patterns or missing them entirely. Recent efforts to test for X-Y sequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…However, studies that have used similar genomic methods across a range of datasets all recovered patterns consistent with this region (Darolti et al 2019;Wright et al 2017;Almeida et al 2020;Fraser et al 2020;Sigeman et al 2021), as have studies using male-specific sequence (Morris et al 2018;Almeida et al 2020;Darolti et al 2020). A recent methodological analysis revealed that the detection of Stratum I in P. reticulata is largely dependent upon the reference genome used (Darolti et al 2022), with studies using reference genomes from distant populations or even different species less able to detect subtle patterns of divergence that characterize the Y chromosome in this species. Our detection of a slight, but non-significant pattern of Fast-X in Stratum I of the Yarra P. reticulata population as well as in the same region of the P. wingei X chromosome gives further weight to the presence of this Stratum.…”
Section: Discussionmentioning
confidence: 91%
“…However, studies that have used similar genomic methods across a range of datasets all recovered patterns consistent with this region (Darolti et al 2019;Wright et al 2017;Almeida et al 2020;Fraser et al 2020;Sigeman et al 2021), as have studies using male-specific sequence (Morris et al 2018;Almeida et al 2020;Darolti et al 2020). A recent methodological analysis revealed that the detection of Stratum I in P. reticulata is largely dependent upon the reference genome used (Darolti et al 2022), with studies using reference genomes from distant populations or even different species less able to detect subtle patterns of divergence that characterize the Y chromosome in this species. Our detection of a slight, but non-significant pattern of Fast-X in Stratum I of the Yarra P. reticulata population as well as in the same region of the P. wingei X chromosome gives further weight to the presence of this Stratum.…”
Section: Discussionmentioning
confidence: 91%
“…Evolutionary strata have been already found also among teleosts, e.g. in guppies (reviewed in Darolti et al 2022) and sticklebacks (Peichel et al 2020; Sardell et al 2021). The older stratum may correspond to the ancestral sex-linked chromosome shared by the Coastal and Inland clades.…”
Section: Discussionmentioning
confidence: 92%
“…However, studies that have used similar genomic methods across a range of datasets all recovered patterns consistent with this region (Almeida et al, 2021; Darolti et al, 2019; Fraser et al, 2020; Sigeman et al, 2022; Wright et al, 2017), as have studies using male‐specific sequence (Almeida et al, 2021; Darolti et al, 2020; Morris et al, 2018). A recent methodological analysis revealed that the detection of Stratum I in P. reticulata is largely dependent upon the reference genome used (Darolti et al, 2022), with studies using reference genomes from distant populations or even different species less able to detect subtle patterns of divergence that characterize the Y chromosome in this species. Our detection of a slight, but non‐significant pattern of Fast‐X in Stratum I of the P. wingei X chromosome gives further weight to the presence of this Stratum.…”
Section: Discussionmentioning
confidence: 99%